Silver ion antibacterial fabric and preparation method thereof
By using silver ion antibacterial fabric in textiles, the fabric consists of a variety of fibers and composite antibacterial fillers, the problem of poor antibacterial effect of existing antibacterial textiles after washing is solved, and long-term antibacterial and comfortable breathable effects are achieved.
Patent Information
- Application Number
- CN202411836932.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-15
AI Technical Summary
Existing antibacterial textiles have poor antibacterial effects after washing, and their comfort is not high, making it difficult to maintain antibacterial properties for a long time.
Silver ion antibacterial fabric is used, which consists of nano-silver ion fibers, chitosan fibers, casein fibers, cotton fibers and composite antibacterial fillers (nano zinc oxide, silver-carrying activated carbon, bamboo charcoal powder). The polymer structure formed by amide bonding and internal and external hydrogen bonds of the molecule enhances antibacterial properties and destroys the bacterial cell structure through the diffusion of silver ions.
It achieves a long-term antibacterial effect, enhances the environmentally friendly degradability and adsorption of the fabric, improves comfort and breathability, and also has a maintenance effect on the skin and improves the body's immunity.
Smart Images

Figure BDA0005186961630000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of antibacterial fabrics, and in particular to silver ion antibacterial fabrics and a preparation method thereof. Background Art
[0002] During exercise, people's body temperature will rise and they will sweat to varying degrees. Although in many cases, sweat will not be visible, this will cause the microclimate between clothing and the human body to be in a high temperature and high humidity state, making it very easy for bacteria to grow on the human skin and clothing that comes into contact with the human skin, affecting people's health. Some resident bacteria on people's skin play a role in protecting the skin from pathogenic bacteria. Once the flora of microorganisms is out of balance, a small number of pathogenic bacteria among them will multiply in large numbers and cause harm to the human body through the skin, respiratory tract, digestive tract and reproductive tract mucosa. As a possible product to prevent and cut off the source of disease infection, antibacterial textiles will play a vital role in people's disease prevention and treatment. Therefore, the design and development of functional clothing with good antibacterial and antibacterial properties has broad development prospects.
[0003] In order to make fiber products have antibacterial properties, the traditional method is to add antibacterial agents to the fiber products. These antibacterial agents not only have poor antibacterial effects, but also have weak binding force with fiber products. After washing several times, the antibacterial agents are basically removed, causing the fiber products to lose their antibacterial efficacy, have poor antibacterial effects, and are not very comfortable. Summary of the invention
[0004] In order to make fiber products have long-lasting antibacterial ability, the present application provides silver ion antibacterial fabric and a preparation method thereof.
[0005] In the first aspect, the present application provides a silver ion antibacterial fabric, which adopts the following technical solution: The silver ion antibacterial fabric comprises the following components in parts by weight: 12-18 parts of nano silver ion fiber, 11-12 parts of chitosan fiber, 5-12 parts of casein fiber, 20-28 parts of cotton fiber, 3-6 parts of composite antibacterial filler, 1-3 parts of dimethyl ester and 50-80 parts of water, wherein the composite antibacterial filler comprises nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder.
[0006] By adopting the above technical scheme, the chitosan fiber and casein fiber structural units are both polymers bonded together by amide bonds. There are more free amino groups in the chitosan molecular structure, and the reaction activity is stronger. The hydroxyl, amino, and N-acetylamino groups distributed on the molecular chain interact with each other to form various intramolecular and intermolecular hydrogen bonds, so that the chitosan fiber has excellent biological functions and can combine with bacteria, fungi, etc., inactivate bacteria and viruses to a certain extent, and has antibacterial, anti-cancer and other properties. Combined with casein fiber, it can increase the environmental degradation and adsorption of antibacterial fabrics, and make the fiber soft and comfortable to wear, and have a certain maintenance effect on the skin. Cotton fiber is added to increase moisture absorption and moisture permeability. The silver ions in the nano silver ion fiber can diffuse into the cells of microorganisms, destroy the protein structure in the cells, cause metabolic disorders of the cells, and thus lead to the death of pathogens.
[0007] The composite antibacterial filler silver-loaded activated carbon can combine with the surface charge of microorganisms, thereby inhibiting the normal development and reproduction of microorganisms. Combined with the electron transition of nano zinc oxide, it can achieve the effect of ultraviolet sterilization. The unique surface and interface effects of bamboo charcoal powder make the composite antibacterial filler have a wider antibacterial effect, and the effect is obvious. They promote each other and play a role in improving the antibacterial effect. Therefore, through the interaction of different substances, the silver ion antibacterial fabric has a broad-spectrum antibacterial effect, and is comfortable, breathable, skin-friendly and maintenance. At the same time, it can also improve the body's immunity.
[0008] In a specific implementation scheme, the mass ratio of the nano zinc oxide, silver-loaded activated carbon, and bamboo charcoal powder is (4-7):(3-5):1.
[0009] By adopting the above technical scheme, a certain proportion of nano zinc oxide, silver-loaded activated carbon, and bamboo charcoal powder are mixed and used as composite antibacterial fillers, which plays a certain role in strengthening the long-term antibacterial effect. Nano zinc oxide improves the ultraviolet sterilization performance of the fabric, and large particles of nano zinc oxide can enhance the antioxidant property of silver-loaded activated carbon, avoiding the deterioration of silver ion antibacterial fabric during use and affecting the activity and use of silver ions, and playing a long-term antibacterial effect; a certain amount of bamboo charcoal powder can be added to improve the comfort of use, soft and skin-friendly. Too much nano zinc oxide can easily reduce the breathability of the fabric, affect the comfort, and reduce the long-term antibacterial effect to a certain extent.
[0010] In a specific embodiment, the particle size of the nano zinc oxide powder is 30-80 nm.
[0011] In a specific embodiment, the silver-loaded activated carbon is silver-loaded nutshell activated carbon with a particle size of 8-60 meshes.
[0012] In a specific embodiment, the preparation method of the nano silver ion fiber is to melt and mix silver ion powder, activated carbon powder, γ-aminopropyltriethoxysilane and polyester chips at 200-240°C, and then add them into a screw extruder for spinning to obtain nano silver ion fiber.
[0013] The mass ratio of the silver ion powder, activated carbon powder and gamma-aminopropyltriethoxysilane is (0.5-1.2):1:(3-8).
[0014] By adopting the above technical scheme, by adding γ-aminopropyltriethoxysilane to silver ion powder and activated carbon powder, the softness and smoothness of the fabric can be improved by utilizing the characteristics of low surface tension and low refractive index of γ-aminopropyltriethoxysilane; and the reasonable ratio of γ-trifluoropropylmethylpolysiloxane and silver ion powder and activated carbon powder can make the two work synergistically to achieve a significant improvement in the antibacterial and softness of the fiber.
[0015] In a second aspect, the present application provides a method for preparing a silver ion antibacterial fabric, using the following technical solution: The preparation method of silver ion antibacterial fabric comprises the following steps: placing nano silver ion fiber, chitosan fiber, chitin fiber and cotton fiber in a blender according to proportion, controlling the rotation speed to be 280-450rpm, stirring for 20-30min, adding composite antibacterial filler, dimethyl ester and water, stirring again, mixing evenly to obtain a mixture, drying, and then subjecting the mixture to coarse yarn, fine yarn, automatic winding, yarn steaming and high-speed paralleling treatment to obtain functional spinning, weaving into fabric, washing and drying to obtain the silver ion antibacterial fabric.
[0016] The second stirring is performed at a rotation speed of 200-240 rpm and a temperature of 50-60°C.
[0017] In summary, the present application includes at least one of the following beneficial technical effects: 1. The structural units of chitosan fiber and casein fiber are both polymers bonded together by amide bonds. There are more free amino groups in the chitosan molecular structure, and the reaction activity is stronger. The hydroxyl, amino, and N-acetylamino groups distributed on the molecular chain interact with each other to form various intramolecular and intermolecular hydrogen bonds, which makes chitosan fiber have excellent biological functions and can combine with bacteria, fungi, etc., inactivating bacteria and viruses to a certain extent. It has antibacterial, anti-cancer and other properties. Combined with casein fiber, it can increase the environmental degradation and adsorption of antibacterial fabrics, and make the fiber soft and comfortable to wear. It has a certain maintenance effect on the skin. Adding cotton fiber increases moisture absorption and permeability. The silver ions in the nano silver ion fiber can diffuse into the cells of microorganisms, destroy the protein structure in the cells, cause metabolic disorders of the cells, and thus lead to the death of pathogens.
[0018] The composite antibacterial filler silver-loaded activated carbon can combine with the surface charge of microorganisms, thereby inhibiting the normal development and reproduction of microorganisms. Combined with the electron transition of nano zinc oxide, it can play a role in ultraviolet sterilization. The unique surface and interface effects of bamboo charcoal powder make the composite antibacterial filler have a wider antibacterial effect, and the effect is obvious. They promote each other and play a role in improving the antibacterial effect. Therefore, through the interaction of different substances, the silver ion antibacterial fabric has a broad-spectrum antibacterial effect, and has the effects of comfort, breathability, skin-friendly maintenance, and can also improve the body's immunity. .
[0019] 2. A certain proportion of nano zinc oxide, silver-loaded activated carbon, and bamboo charcoal powder are mixed and used as composite antibacterial fillers to enhance the long-term antibacterial effect. Nano zinc oxide improves the UV sterilization performance of the fabric, and large particles of nano zinc oxide can enhance the antioxidant properties of silver-loaded activated carbon, preventing the silver ion antibacterial fabric from deteriorating during use and affecting the activity and feel of the silver ions, thus achieving a long-term antibacterial effect. A certain amount of bamboo charcoal powder can be added to improve the comfort of use and make it soft and skin-friendly. Too much nano zinc oxide can easily reduce the breathability of the fabric, affecting the comfort level, and also reducing the long-term antibacterial effect to a certain extent. DETAILED DESCRIPTION
[0020] The present application is further described in detail below in conjunction with embodiments.
[0021] Nano zinc oxide powder, item number 100367, was purchased from Xianfeng Nano; silver-loaded activated carbon was silver-loaded nut shell activated carbon, model: YYCOZ; chitosan fiber was purchased from Qingdao Jifa New Materials Co., Ltd.; casein fiber was purchased from Shanghai Zhengjia; cotton fiber was kapok fiber purchased from Dongguan Weixin Import and Export Co., Ltd.; dimethyl ester was dimethyl carbonate purchased from Shandong Xinyujia Chemical Co., Ltd.; bamboo charcoal powder (200 mesh) was purchased from Hubei Tongke Activated Carbon Co., Ltd.; polyester chips were purchased from Shandong Shunxinlong New Materials Technology Co., Ltd.
[0022] The raw materials used in the examples and comparative examples that are not otherwise specified are all conventional products that can be purchased from the market.
[0023] Preparation Example Preparation of Nano Silver Ion Fiber: Preparation Example 1 0.5 kg of silver ion powder, 1 kg of activated carbon powder, 3 kg of γ-aminopropyltriethoxysilane and 10 kg of polyester chips were melt-mixed at 240° C. and then added into a screw extruder for spinning to obtain nano silver ion fibers.
[0024] Preparation Example 2 1.2 kg of silver ion powder, 1 kg of activated carbon powder, 8 kg of γ-aminopropyltriethoxysilane and 10 kg of polyester chips were melt-mixed at 200° C. and then added into a screw extruder for spinning to obtain nano silver ion fibers.
[0025] Preparation Example 3 2.2 kg of silver ion powder, 1 kg of activated carbon powder, 7 kg of γ-aminopropyltriethoxysilane and 10 kg of polyester chips were melt-mixed at 200° C. and then added into a screw extruder for spinning to obtain nano silver ion fibers.
[0026] Preparation Example 4 1.2 kg of silver ion powder, 9 kg of γ-aminopropyltriethoxysilane and 10 kg of polyester chips were melt-mixed at 200° C. and then added into a screw extruder for spinning to obtain nano silver ion fibers. Example
[0027] Example 1 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 1, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder, and the mass ratio of nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder is 4:5:1; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0028] Example 2 The silver ion antibacterial fabric comprises the following components in parts by weight: 18 g of the nano silver ion fiber prepared in Preparation Example 1, 11 g of chitosan fiber, 12 g of casein fiber, 20 g of cotton fiber, 6 g of composite antibacterial filler, 1 g of dimethyl ester and 80 g of water, wherein the composite antibacterial filler is nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder, and the mass ratio of nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder is 4:5:1; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 450rpm, and after stirring for 20 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 240rpm, the temperature is 50℃, and the mixture is stirred and mixed again to obtain a mixture, which is dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0029] Example 3 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 1, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder, and the mass ratio of nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder is 7:3:1; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0030] Example 4 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 1, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder, and the mass ratio of nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder is 6:3:1; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0031] Example 5 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 2, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder, and the mass ratio of nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder is 4:5:1; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0032] Example 6 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 3, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder, and the mass ratio of nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder is 4:5:1; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0033] Example 7 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 4, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder, and the mass ratio of nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder is 4:5:1; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0034] Example 8 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 1, 5 g of casein fiber, 40 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder, and the mass ratio of nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder is 4:5:1; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0035] Example 9 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 1, 12 g of chitosan fiber, 33 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder, and the mass ratio of nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder is 4:5:1; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0036] Comparative Example 1 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 1, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is nano zinc oxide; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0037] Comparative Example 2 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 1, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is silver-loaded activated carbon; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0038] Comparative Example 3 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 1, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is bamboo charcoal powder; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0039] Comparative Example 4 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 1, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is nano zinc oxide and silver-loaded activated carbon, and the mass ratio of nano zinc oxide to silver-loaded activated carbon is 4:6; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0040] Comparative Example 5 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 1, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is nano zinc oxide and bamboo charcoal powder, and the mass ratio of nano zinc oxide to bamboo charcoal powder is 9:1; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0041] Comparative Example 6 The silver ion antibacterial fabric comprises the following components in parts by weight: 12 g of the nano silver ion fiber prepared in Preparation Example 1, 12 g of chitosan fiber, 5 g of casein fiber, 28 g of cotton fiber, 3 g of composite antibacterial filler, 3 g of dimethyl ester and 50 g of water, wherein the composite antibacterial filler is silver-loaded activated carbon and bamboo charcoal powder, and the mass ratio of the silver-loaded activated carbon to the bamboo charcoal powder is 5:5; Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the speed is controlled to be 280rpm, and after stirring for 30 minutes, the composite antibacterial filler, dimethyl ester and water are added, the speed is adjusted to 200rpm, the temperature is 60℃, and the mixture is stirred and mixed again to obtain a mixture, which is then dried, and then processed through roving, spun yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics with a warp density of 85 strands / cm and a weft density of 55 strands / cm. The fabrics are washed with water and dried at 70℃ to obtain silver ion antibacterial fabrics.
[0042] Performance Testing For the silver ion antibacterial fabrics prepared in the examples and comparative examples, the test standards are as follows: Antibacterial rate test: Antibacterial rate test is carried out according to GB / T20944.3-2008; For the softness test, a 5-person 10-point scoring method was used to touch and score each group of silver ion antibacterial fabrics, and the average value was taken; the test results are shown in the table below.
[0043] Combined with the table, the silver ion antibacterial fabrics of Example 1 and Comparative Examples 1-6 are compared. The results show that the mixed use of nano zinc oxide, silver-loaded activated carbon, and bamboo charcoal powder in a certain proportion as a composite antibacterial filler plays a certain role in strengthening the long-term antibacterial effect. Nano zinc oxide improves the ultraviolet sterilization performance of the fabric, and large particles of nano zinc oxide can enhance the antioxidant property of silver-loaded activated carbon, avoiding the deterioration of the silver ion antibacterial fabric during use and affecting the activity and use of silver ions, and playing a long-term antibacterial effect; a certain amount of bamboo charcoal powder can be added to improve the comfort of use, soft and skin-friendly. Too much nano zinc oxide can easily reduce the air permeability of the fabric, affect the comfort, and reduce the long-term antibacterial effect to a certain extent.
[0044] By comparing Example 1 with Examples 5-7, it can be seen that by adding γ-aminopropyltriethoxysilane to the silver ion powder and activated carbon powder, the softness and smoothness of the fabric can be improved by utilizing the characteristics of low surface tension and low refractive index of γ-aminopropyltriethoxysilane; and the reasonable ratio of γ-trifluoropropylmethylpolysiloxane and silver ion powder and activated carbon powder can enable the synergistic effect of the two to achieve a significant improvement in the antibacterial properties and softness of the fiber.
[0045] By comparing Example 1 with Examples 8-9, it can be seen that the mixture of chitosan fiber, casein fiber and cotton fiber has a certain synergistic effect of improving the comfort and antibacterial properties of the fabric; there are more free amino groups in the chitosan molecular structure, and the reaction activity is stronger. It has excellent biological functions and can combine with bacteria, fungi, etc., and inactivate bacteria, viruses, etc. to a certain extent. Combined with casein fiber, it can increase the environmental degradation and adsorption of the antibacterial fabric, and make the fiber soft to the touch, comfortable to wear, and have a certain maintenance effect on the skin.
[0046] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. Silver ion antibacterial fabric, characterized in that: The invention comprises the following components in parts by weight: 12-18 parts of nano silver ion fiber, 11-12 parts of chitosan fiber, 5-12 parts of casein fiber, 20-28 parts of cotton fiber, 3-6 parts of composite antibacterial filler, 1-3 parts of dimethyl ester and 50-80 parts of water. The composite antibacterial filler comprises nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder.
2. The silver ion antibacterial fabric according to claim 1, characterized in that: The mass ratio of the nano zinc oxide, silver-loaded activated carbon and bamboo charcoal powder is (4-7): (3-5):
1.
3. The silver ion antibacterial fabric according to claim 1, characterized in that: The particle size of the nano zinc oxide powder is 30-80nm.
4. The silver ion antibacterial fabric according to claim 1, characterized in that: The silver-loaded activated carbon is silver-loaded nutshell activated carbon with a particle size of 8-60 meshes.
5. The silver ion antibacterial fabric according to claim 1, characterized in that: The preparation method of the nano silver ion fiber is as follows: silver ion powder, activated carbon powder, γ-aminopropyl triethoxysilane and polyester chips are melt-mixed at 200-240° C., and then added into a screw extruder for spinning to obtain the nano silver ion fiber.
6. The silver ion antibacterial fabric according to claim 1, characterized in that: The mass ratio of the silver ion powder, activated carbon powder and γ-aminopropyltriethoxysilane is (0.5-1.2):1:(3-8).
7. The method for preparing the silver ion antibacterial fabric according to any one of claims 1 to 6, characterized in that: The following steps are involved: Nano silver ion fiber, chitosan fiber, casein fiber and cotton fiber are placed in a blender in proportion, the rotation speed is controlled to be 280-450 rpm, and after stirring for 20-30 minutes, the composite antibacterial filler, dimethyl ester and water are added, and stirred again. After uniform mixing, the mixture is dried, and then processed through coarse yarn, fine yarn, automatic winding, steaming yarn, and high-speed paralleling to obtain functional spinning, which is woven into fabrics, and washed and dried to obtain silver ion antibacterial fabrics.
8. The method for preparing the silver ion antibacterial fabric according to claim 7, characterized in that: The second stirring is performed at a rotation speed of 200-240 rpm and a temperature of 50-60°C.